Getting smart : how digital learning is changing the world - Vander Ark, Tom, 1959- (San Francisco, CA. : Jossey-Bass, 2012)
'A comprehensive look at the promise and potential of online learning In our digital age, students have dramatically new learning needs and must be prepared for the idea economy of the future. In Getting Smart, well-known global education expert Tom Vander Ark examines the facets of educational innovation in the United States and abroad. Vander Ark makes a convincing case for a blend of online and onsite learning, shares inspiring stories of schools and programs that effectively offer'personal digital learning' opportunities, and discusses what we need to do to remake our schools into'smart schools.' Examines the innovation-driven world, discusses how to combine online and onsite learning, and reviews'smart tools' for learning Investigates the lives of learning professionals, outlines the new employment bargain, examines online universities and'smart schools' Makes the case for smart capital, advocates for policies that create better learning, studies smart cultures '--
Includes bibliographical references and index.
Keywords: Computer-assisted instruction -- United States; Internet in education -- United States; Blended learning -- United States